Solidarność 84 [kartka pocztowa] . Solidarity 84. Postcard (Polska, 1984)
Black and red print on white paper. Postcard, with undivided back, contains graphic image which represents four boys, numbered 81-84. Boy no. 84 sits on a windowsill of a window with bars.